Potential Monopoly Issues in the Grab–GOTO Merger Plan: An Analysis Under Indonesian Competition Law - Lie , Cathleen; Lie, Gunardi (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study examines the potential monopolistic effects arising from the planned merger between Grab and Gojek, two dominant digital transportation platforms in Indonesia. As multi-sided markets characterized by strong network effects, ride-hailing platforms naturally tend toward high market concentration. The merger is projected to create a combined market share exceeding 90% and elevate the market's Herfindahl–Hirschman Index (HHI) far above conventional antitrust thresholds. Using a normative legal method supported by statutory analysis and the economic analysis of law, this research evaluates whether such a merger may violate Indonesia’s Law No. 5 of 1999 concerning anti-monopoly and unfair business competition, particularly regarding monopoly formation, dominant position, and anti-competitive mergers. The results indicate that the merger carries a high risk of creating a monopoly structure, increasing entry barriers, reducing consumer welfare, weakening drivers’ bargaining power, and enabling potential abuse of dominance. It is recommended that the Indonesian Competition Commission (KPPU) impose strong structural remedies or prohibit the merger entirely to preserve healthy competition in the digital platform industry.